THE EFFECT OF SOIL-COCOFIBER MEDIA COMPOSITION ON THE GROWTH OG WHITE TEAK SEEDLINGS (Gmelina arborea Roxb) - Wahyuni, Sri; Idris, Andi Irmayanti; Rusmidin, Rusmidin (Universitas Gorontalo, 2026)
Cocofiber is a product of coconut fiber decomposition, the combination of cocofiber and soil can optimize plant growth and improve soil drainage and increase soil water retention capacity. The purpose of this study was to determine the Effect of Soil and Cocofiber Media Composition on the Growth of White Teak Seedlings (Gmelina Atborea Roxb). This research was conducted in Bonra Village, Mapilli District, Polewali Mandar Regency from August to December 2024. The data collection technique used quantitative data using a Randomized Block Design (RAK) consisting of 5 treatments, 6 replications, 6 groups of observation time. The treatments used were P0 (100% cocofiber), P1 (100% soil), P2 (1 soil: 1 cocofiber), P3 (2 soils: 1 cocofiber), P4 (2 cocofibers: 1 soil). The parameters observed were the increase in the height of white teak seedlings, the increase in the diameter of white teak seedlings, and the increase in the number of leaves of white teak seedlings. Analysis was conducted by comparing the calculated F to the F table. If the calculated F was greater than the F table at the 5% level, Duncan's further test was performed. The results of this study indicate that the best treatment for increasing white teak seedling height was P3: 2 soil: 1 cocofiber; the best dose for increasing white teak seedling diameter was P1: 100% soil; and the best dose for increasing leaf number was P2: 1 soil: 1 cocofiber.